The Potential Role for a Nitrogen Compliance Policy in Mitigating Gulf Hypoxia. (29th December 2016) - Ribaudo, Marc; Key, Nigel; Sneeringer, Stacy
Abstract: We evaluate whether expanding compliance to include nitrogen management could be an effective tool to reduce excess nitrogen applications in the Mississippi and Atchafalaya River Basin (MARB). Compliance requires farmers to meet some minimum standard of environmental protection on environmentally sensitive land as a condition for receiving federal farm program benefits. Using farm‐level data on "excess" nitrogen applications and program benefits, we estimate the level of compliance and the reduction in excess nitrogen applications to cropland in the MARB. Extending compliance provisions to nitrogen management could reduce excess applications up to 60% under ideal conditions.